2021
DOI: 10.3390/cancers13174298
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Ultrasound Fine-Needle Biopsy versus Fine-Needle Aspiration for Tissue Sampling of Abdominal Lymph Nodes: A Propensity Score Matched Multicenter Comparative Study

Abstract: There is a paucity of evidence on the comparison between endoscopic ultrasound (EUS) fine-needle biopsy (FNB) and fine-needle aspiration (FNA) for lymph node (LNs) sampling. The aim of this study was to compare these two approaches in a multicenter series of patients with abdominal tumors. Out of 502 patients undergoing EUS sampling, two groups following propensity score matching were compared: 105 undergoing EUS-FNB and 105 undergoing EUS-FNA. The primary outcome was diagnostic accuracy. Secondary outcomes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…While EUS-FNA may still play a competitive role as compared to EUS-FNB when rapid-on-site cytological evaluation (ROSE) is available, EUS-FNB was found to overperform standard FNA for tissue sampling of several solid lesions in the absence of a pathologist in the endoscopic room [ 3 , 4 , 5 , 6 ]. Moreover, in spite of the favorable diagnostic outcomes of EUS through-the-needle biopsy (TTNB) and confocal laser endomicroscopy (CLE), EUS-FNA is still frequently used in the diagnostic algorithm of cystic pancreatic lesions (PCLs) [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…While EUS-FNA may still play a competitive role as compared to EUS-FNB when rapid-on-site cytological evaluation (ROSE) is available, EUS-FNB was found to overperform standard FNA for tissue sampling of several solid lesions in the absence of a pathologist in the endoscopic room [ 3 , 4 , 5 , 6 ]. Moreover, in spite of the favorable diagnostic outcomes of EUS through-the-needle biopsy (TTNB) and confocal laser endomicroscopy (CLE), EUS-FNA is still frequently used in the diagnostic algorithm of cystic pancreatic lesions (PCLs) [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a most recent study comparing the EUS-guided fine needle biopsy (FNB) vs. EUS-guided FNA in abdominal LN lesions, diagnostic accuracy was significantly higher in the EUS-FNB group as compared to the EUS-FNA group (87.62% versus 75.24%, P = 0:02). These findings suggested that EUS-FNB can be preferred to EUS-FNA for sampling intra-abdominal LNs in patients with suspected malignancy [23].…”
Section: Discussionmentioning
confidence: 93%
“…The use of EUS-FNB needles has generated a great deal of interest in the field of EUS-TA for several abdominal and submucosal lesions [19,20,21] primarily based on proposed advantages over EUS-FNA needles, namely improving diagnostic accuracy, improving procurement of samples with preserved tissue architecture, and allowing for immunohistochemistry or special stains required for certain diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Attention should be paid to pneumothorax, but when a pulmonary mass is so close to the esophagus to be seen with ultrasound, no air is in between the two structures and the risk of pneumothorax is very low when the needle moves inside the solid mass. The use of EUS-FNB needles has generated a great deal of interest in the field of EUS-TA for several abdominal and submucosal lesions [19,20,21] primarily based on proposed advantages over EUS-FNA needles, namely improving diagnostic accuracy, improving procurement of samples with preserved tissue architecture, and allowing for immunohistochemistry or special stains required for certain diagnoses.…”
Section: Discussionmentioning
confidence: 99%